A review on membrane concentrate management from landfill leachate treatment plants: The relevance of resource recovery to close the leachate treatment loop. Issue 2 (February 2023) - de Almeida, Ronei; Porto, Raphael Ferreira; Quintaes, Bianca Ramalho; Bila, Daniele Maia; Lavagnolo, Maria Cristina; Campos, Juacyara Carbonelli
Membrane filtration processes have been used to treat landfill leachate. On the other hand, closing the leachate treatment loop and finding a final destination for landfill leachate membrane concentrate (LLMC) – residual stream of membrane systems – is challenging for landfill operators. The re-introduction of LLMC into the landfill is typical; however, this approach is critical as concentrate pollutants may accumulate in the leachate treatment facility. From that, leachate concentrate management based on resource recovery rather than conventional treatment and disposal is recommended. This work comprehensively reviews the state-of-the-art of current research on LLMC management from leachate treatment plants towards a resource recovery approach. A general recovery train based on the main LLMC characteristics for implementing the best recovery scheme is presented in this context. LLMCs could be handled by producing clean water and add-value materials. This paper offers critical insights into LLMC management and highlights future research trends.